Efficacy and safety of first-line immunotherapy and targeted therapy in advanced HCC: a network meta-analysis with subgroup analysis based on HBV and HCV infection - Li, Qinfei; Li, Hong; Ma, Haowei; Chen, Wei (Frontiers in Immunology, 2026)
IntroductionWe conducted an etiology-stratified network meta-analysis of first-line systemic therapies for advanced HCC to compare newer regimens beyond sorafenib-based RCT evidence (HBV, HCV, or non-viral).MethodsFollowing PRISMA-NMA, we searched PubMed, Embase, Cochrane Library, and Web of Science to 01 June 2025 for first-line RCTs in advanced/unresectable HCC. Primary endpoints were overall survival (OS) and progression-free survival (PFS); secondary endpoints were objective response rate (ORR) and grade ≥3 adverse events (AEs≥3). A Bayesian fixed-effects NMA (gemtc v4.4 with rjags) reported hazard ratios (HRs) or risk ratios (RRs) with 95% credible intervals, calculated SUCRA values for ranking, and assessed network coherence using deviance information criterion differences between consistency and inconsistency models. Protocol registered in PROSPERO (CRD420251074687).ResultsTwenty-four RCTs (n=13,572) evaluating 26 first-line regimens formed a connected evidence network. In the overall population, regimens with significant OS advantage over sorafenib included sintilimab plus bevacizumab biosimilar (HR = 0.57, 95% CrI 0.43–0.75), camrelizumab plus rivoceranib (HR = 0.62, 0.48–0.79), and atezolizumab plus bevacizumab (HR = 0.66, 0.51–0.84). For PFS, top-ranked combinations were camrelizumab plus rivoceranib (HR = 0.52, 0.41–0.66), anlotinib plus penpulimab (HR = 0.53, 0.41–0.68), lenvatinib plus pembrolizumab (HR = 0.55, 0.44–0.68), and sintilimab plus bevacizumab biosimilar (HR = 0.56, 0.45–0.69). ORR was highest with lenvatinib plus pembrolizumab (RR = 8.00, 4.98–12.86). Regarding safety, tislelizumab (RR = 0.42, 0.33–0.52) and nivolumab (RR = 0.45, 0.36–0.56) were associated with the lowest incidence of AEs≥3. Etiology-stratified analyses indicated that, in HBV-related HCC, sintilimab plus bevacizumab biosimilar and atezolizumab plus bevacizumab led OS rankings, with PFS favoring cabozantinib plus atezolizumab and atezolizumab plus bevacizumab. In HCV-related HCC, only atezolizumab plus bevacizumab conferred a significant OS benefit (HR = 0.43, 0.25–0.73), while PFS superiority was observed only for cabozantinib plus atezolizumab (HR = 0.73, 0.54–0.99). In non-viral HCC, the STRIDE regimen (single priming dose tremelimumab plus durvalumab) was the only regimen to significantly improve OS (HR = 0.75, 0.59–0.96).ConclusionsFor first-line therapy in advanced HCC, ICI-based combinations with anti-VEGF/anti-angiogenic agents generally outperform sorafenib, with discernible etiology-specific optima: HBV-related HCC favors sintilimab plus bevacizumab biosimilar or atezolizumab plus bevacizumab; HCV-related HCC favors atezolizumab plus bevacizumab; and in non-viral disease, STRIDE demonstrates a unique OS advantage. This etiology-stratified evidence framework may guide individualized first-line decision-making, pending confirmation in head-to-head trials.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD420251074687, CRD420251074687.